Handbook of psycholinguistics - Traxler, Matthew J.; Gernsbacher, Morton Ann. (Amsterdam ; Boston : Elsevier/Academic Press, 2006)
With Psycholinguistics in its fifth decade of existence, the second edition of the Handbook of Psycholinguistics represents a comprehensive survey of psycholinguistic theory, research and methodology, with special emphasis on the very best empirical research conducted in the past decade. Thirty leading experts have been brought together to present the reader with both broad and detailed current issues in Language Production, Comprehension and Development. The handbook is an indispensible single-source guide for professional researchers, graduate students, advanced undergraduates, university and college teachers, and other professionals in the fields of psycholinguistics, language comprehension, reading, neuropsychology of language, linguistics, language development, and computational modeling of language. It will also be a general reference for those in neighboring fields such as cognitive and developmental psychology and education. *Provides a complete account of psycholinguistic theory, research, and methodology *30 of the field's foremost experts have contributed to this edition *An invaluable single-source reference.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Psycholinguistics; Electronic books